Vaccine eagerness: A new framework to analyse preferences in single profile discrete choice experiments. Application to HPV vaccination decisions among French adolescents. (March 2022) - Chyderiotis, Sandra; Sicsic, Jonathan; Thilly, Nathalie; Mueller, Judith E.; ,; Stéphanie, Bonnay; Céline, Pulcini; Nelly, Agrinier; Estelle, Fall; Serge, Gilberg; Sébastien, Bruel; Henri, Partouche; et al.
Abstract: Background: We previously conducted a single-profile discrete choice experiment to elicit preferences of adolescents around HPV vaccine communication, finding that only half of participants made variable choices (non-uniform respondents) from which preferences were elicited. In this paper we provide a framework to evaluate post-choice certainty information to elicit preferences even among respondents who uniformly accepted (serial demanders) or refused (serial non-demanders) hypothetical vaccination scenarios. Methods: During an in-class online questionnaire among 1458 French adolescents aged 13–15 years old, we collected certainty levels (0–10) after decisions on nine hypothetical scenarios, including four vaccination attributes: information on vaccine-preventable disease type, on vaccine safety, on potential for indirect protection and on vaccine coverage. We developed a vaccine eagerness scale (ranging from −10 to 10), by combining information on the binary decision (accept vs. refuse the hypothetical vaccine) and the decision certainty level. We used random effects linear regressions to evaluate attributes' impact on vaccine eagerness. Sensitivity analyses were performed taking into account low response quality, assessed as invariant certainty and low response time. Results: Attributes' impact on decision certainty were similar between serial demanders (N = 659) and non-uniform respondents (N = 711): mentioning a positive benefit-risk balance significantly decreased certainty to accept (coefficient −0.93), while information on 80% coverage in other countries (+0.33) and potential for disease elimination (+0.09) increased it. Among serial non-demanders, significant attribute impacts were observed only after exclusion of low-quality responses (N = 31): a potential for disease elimination (coefficient: +0.24) and 80% coverage in other countries (+0.42) significantly increased certainty of refusing vaccination. Combining decision and certainty into a vaccine eagerness indicator allowed analysing preferences in the full sample, including "hesitant" respondents, who were sensitive to the content of the vaccination profile. Conclusion: Choice certainty informs on respondents' preferences in single-profile discrete-choice experiments, in particular among those with uniform responses. Highlights: Preferences are not identified among "uniform respondents" in single profile DCEs. Analysis of post-choice certainty can reveal information on their preferences. We propose a new concept for DCEs on vaccination, "vaccine eagerness". Vaccine eagerness allows analyzing preferences among serial non-demanders.